Impact of pure pasture and silvopastoral systems on carbon and nitrogen in sodic soils of the dry chaco - Banegas, Natalia Romina; Dos Santos, Daniel Andrés; Viruel, Emilce; Gasparri, Néstor Ignacio (Springer, 2025)
Grazing and silvopastoral systems represent effective strategies for enhancing soil organic carbon (SOC) and total nitrogen (tN) content in sodic soils. This study assessed alternative cattle production systems over 6 years to increase SOC and tN levels at different soil depths, analyzing mineral-associated (AOC) and particulate organic carbon (POC) fractions to understand SOC dynamics. The experimental design included two management practices, each covering 9 hectares: pure pasture (PP) and silvopastoral systems (SPS). Within the silvopastoral area, two subsections were distinguished: under tree canopy (SPS-UC) and between tree canopies (SPS-BC), corresponding to alternating bands defined by rows of Neltuma alba (syn. Prosopis alba). All plots were cultivated with Chloris gayana cv. Epica INTA-Pemán. Statistical analyses focused on evaluating the impacts of these treatments, temporal effects (four yearly time points), and their interactions on SOC, POC, AOC, and tN. Significant differences were observed in the distribution of SOC, POC, AOC, and tN between PP and SPS systems. Notably, SPS-BC exhibited the lowest SOC and tN values. Both PP and SPS-UC showed increases in SOC within the top 50 cm of soil depth, primarily attributed to elevated AOC levels. These findings underscore the potential of pure pasture and silvopastoral systems to enhance soil fertility through increases in soil organic matter, thereby improving the productive potential of sodic soils. Moreover, the study highlights the necessity for further research in silvopastoral systems, with a high possibility in implementation for livestock production in Dry Chaco, to investigate how different tree configurations influence SOC and tN dynamics in these soils.